HOW DO YOU BEAT THE BARRIERS? INVESTIGATING THE CRITICAL SUCCESS FACTORS OF MANAGING EVENT DURING COVID-19 PANDEMIC - Mohamad Sayuti Md Saleh; Nurfatihah S Baharuddin; Mohamad Rahimi Mohamad Rosman; Faizal Haini Fadzil; Nurulannisa Abdullah; Mohd Zafian Mohd Zawawi; Izzatil Husna Arshad (International Journal of Accounting, Finance and Business, 2022)
Event management is a multi-billion industry that was greatly hampered by the pandemic of COVID-19. The aftermath of the COVID-19 pandemic saw many players go out of business, facing liquidation, or cease of operation. Thus, there is growing interest in the need to identify the critical success factors for organizing events in the aftermath of the COVID-19 pandemic. Therefore, a mixed-method approach was adopted. Data was analyses based on descriptive analysis; findings indicated that several elements influence the success factors of an event in the aftermath of COVID-19, such as engagement, reward, peer influences, communication, promotion, and information system friendliness.